1996
DOI: 10.1007/s002849900046
|View full text |Cite
|
Sign up to set email alerts
|

Glycoside and Polysaccharide Hydrolase Activity of the Rumen Anaerobic Fungus Caecomyces communis ( Sphaeromonas communis SENSU ORPIN) at Early and Final Stages of the Developmental Cycle

Abstract: The rumen anaerobic fungus Caecomyces communis was grown in a fermentor in Lowe medium. We studied four polysaccharide hydrolases and three glycoside hydrolases at early and final stages. We found a difference in cell association for these enzymes depending on the developmental stage. The endocellulase and beta-D-fucosidase were early synthesized, and their activities decreased at the end of the developmental cycle. On the contrary, the beta-D-glucosidase, beta-D-xylosidase and xylanase activities increased du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…This result indicates that such fibrolytic ruminal fungal strains are prevalent in grazing ruminants such as grazing yaks, Tibetan sheep and Small Tail Han sheep, and could be exploited as microbial feed additives to improved fiber utilization in ruminants from intensive farming. In addition, we found that the relative abundance of genera Piromyces and Neocallimastix were significant higher in Tibetan sheep in comparison to yak, suggesting that the Tibetan sheep have the relatively high ability to utilize recalcitrant material (cellulose and hemicellulose) considering these two genera are capable of producing cellulolytic and hemicellulolytic enzymes [46]. Additionally, many previous studies have discovered genus Neocallimastix was dominant in many ruminant species, such as American bison, sheep and llama [5,24,47], which was less abundant in the current study.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This result indicates that such fibrolytic ruminal fungal strains are prevalent in grazing ruminants such as grazing yaks, Tibetan sheep and Small Tail Han sheep, and could be exploited as microbial feed additives to improved fiber utilization in ruminants from intensive farming. In addition, we found that the relative abundance of genera Piromyces and Neocallimastix were significant higher in Tibetan sheep in comparison to yak, suggesting that the Tibetan sheep have the relatively high ability to utilize recalcitrant material (cellulose and hemicellulose) considering these two genera are capable of producing cellulolytic and hemicellulolytic enzymes [46]. Additionally, many previous studies have discovered genus Neocallimastix was dominant in many ruminant species, such as American bison, sheep and llama [5,24,47], which was less abundant in the current study.…”
Section: Discussionmentioning
confidence: 82%
“…Recent studies on dairy cows have found that Caecomyces was the second most dominant genus [11,45], while in the present study, Piromyces was the second prevalent genus in the rumen, irrespective of animal species, but the relative abundance of genus Caecomyces was very low (0.76%). Previous study has reported that the genus Piromyces can produce cellulolytic and hemicellulolytic enzymes [46,47], while members (Caecomyces communis) belonging to genus Caecomyces had glycoside and polysaccharide hydrolase activity. This result indicates that such fibrolytic ruminal fungal strains are prevalent in grazing ruminants such as grazing yaks, Tibetan sheep and Small Tail Han sheep, and could be exploited as microbial feed additives to improved fiber utilization in ruminants from intensive farming.…”
Section: Discussionmentioning
confidence: 99%
“…The top 20 positively correlated B. cinerea genes contained all seven genes involved in BOT biosynthesis (Deighton et al, 2001; Colmenares et al, 2002; Wang et al, 2009; Rossi et al, 2011; Ascari et al, 2013; Porquier et al, 2016). In addition to phytotoxins, more than 30 genes of the top 100 lesion-correlated genes encode plant cell wall degrading enzymes, that is glucosyl hydrolases, carbohydrate esterases, cellobiose dehydrogenases and Bcpg1 (Figure 3 and Figure 3—source data 1) (Gerbi et al, 1996; Zamocky et al, 2006; Cantarel et al, 2009; Van Vu et al, 2012; Igarashi et al, 2014; Morgenstern et al, 2014; Blanco-Ulate et al, 2014; Tan et al, 2015; Courtade et al, 2016; Nelson et al, 2017; Pérez‐Izquierdo et al, 2017). Additionally, 10 of the top 100 lesion-correlated genes were annotated as putative peptidase activities, which are critical for fungal virulence (Movahedi et al, 1991; Poussereau et al, 2001a; Poussereau et al, 2001b; ten Have et al, 2004; ten Have et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Habitat: rumen and intestinal tract of large herbivorous animals Anaeromyces mucronatus 543 40 Caecomyces communis 41 Cyllamyces aberensis 42 Neocallimastix frontalis 43 Orpinomyces sp. 44 Piromyces sp.…”
Section: Anaerobic Fungimentioning
confidence: 99%